Amelioration of The Dielectric Properties of Ceramic Insulators Using Nano-alumina - S. M. A. El-Gamal; M. A. Abd-Allah; Eman Belal Ahmad; T. Eliyan; Osama A. Desouky (Universitas Diponegoro, 2021)
Outdoor HV porcelain insulators face various environmental stresses that cause their degradation. Consequently, amelioration of their insulating properties becomes a target of recent researches to survive higher voltage levels. Investigating the impact of the addition of 0, 5, 10, and 15 wt. % nano- alumina (NA) on the dielectric and physical characteristics of porcelain materials at elevated sintering temperatures is the aim of this study. Porcelain specimens were synthesized from kaolin, feldspar, and quartz as available low-cost raw materials. The specimens were sintered at 1100, 1200, 1300, and 1400°C for 2 h. For some specimens, the microstructure and phases formed were identified using scanning electron microscopy and X-ray diffraction techniques. The changes that occur upon heating (include melting, phase transition, sublimation, and decomposition) were identified by Differential Thermogravimetric Analysis. The dielectric strength, relative permittivity, and loss tangent of different samples were measured at a large scale of frequencies. Breakdown strength values of different samples were verified by applying the Finite Element Method. The best electrical and physical properties were achieved at 1300ºC. At this temperature the porcelain sample containing 5 wt. % NA presented optimum physical characteristics as well as good insulating properties assent the feasibility of producing electro-technical porcelain